Context matters: examining factors influencing the implementation of evidence-based family systems care for small and sick newborns across the care continuum - Christina Schuler; Christina Schuler; Faith Agbozo; Emmanuel Bansah; Barbara Preusse-Bleuler; Richard Owusu; Riccardo E. Pfister; Riccardo E. Pfister (Frontiers in Health Services)
IntroductionThe health and wellbeing of small and sick newborns and their families can be enhanced through family systems care (FSC) along the care continuum. FSC encompasses a broader approach than family-centered care. FSC identifies individual and family strengths while acknowledging illness-related suffering and providing expertise to help soften it through relational family systemic interventions. Contextual factors of the targeted healthcare setting need to be understood to implement FSC. This study aims to assess healthcare professionals’ perceptions of health system features that may influence the successful context-adapted implementation of FSC into the care continuum for small and sick newborns and their families in the Ghanaian healthcare setting.MethodsCross-sectional data were collected from 143 healthcare professionals, comprising nurses, midwives, and physicians who provide maternal and newborn care at a secondary facility and 13 primary health facilities in the Hohoe Municipality, Ghana. The Context Assessment for Community Health (COACH) instrument, employing Likert scales ranging from 1 to 5 and including questions on training history, was used to collect data on FSC through self-administered interviews. Data were analyzed using descriptive statistics with STATA.ResultsWhile 48.9% of healthcare professionals reported never receiving any didactic or school-based training, the majority (96.5%) indicated a need for in-service training in FSC. From the highest score of 5, the COACH dimension for organizational resources had the lowest score (2.8). Community engagement, commitment to work, monitoring services for action, and informal payment reported scores between 3.7 and 3.9. The highest scores were reported for the leadership and work culture dimensions, at 4.1 and 4.2, respectively. Among the different units of the care continuum, the largest variations were observed in the subdimensions of organizational resources (2.5–3.4) and informal payment (3.6–4.4).ConclusionThe COACH tool provided contextual guidance for developing training strategies to implement a contextually appropriate FSC program in Ghana, which is likely to be adaptable and relevant in other low- and middle-income countries. Healthcare professionals perceive themselves as committed, with a favorable work culture and a positive perception toward their leaders, but they report limited resources and challenges in accessing knowledge sources. These findings indicate a readiness for FSC training along the continuum of care in the perinatal period.